Efektifitas Pendampingan Minum Tablet Tambah Darah (TTD) Oleh Kader Posyandu terhadap Peningkatan Kadar Hb Ibu Hamil di Puskesmas Kota Palangka Raya - Seri Wahyuni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Anemia is one of the indirect causes of maternal mortality. The Government of Indonesia has made efforts to overcome anemia, including by giving iron tablets to pregnant women. To improve maternal compliance in consuming iron tablet healthcare workers should include family/cadres in the supervision of food and medicine. This study aims to know the effectiveness of accompaniment drinking iron tablet By Cadres Against Increasing Hb Level of Pregnant Women at Puskesmas Kota Palangka Raya. This research is a quasi-experimental design using